Development of an Automated Model for Evaluating the Reproduction of Fixed Assets of the Enterprises of Hotel Industry - LUCHYK, Svitlana D.; MUSTETSA, Iryna V.; BAGRII, Konon L.; MANACHYNSKA, Yulia A.; YEVDOSHCHAK, Volodymyr I. (Journal of Environmental Management and Tourism; Vol 10 No 6 (2019): JEMT Volume X Issue 6(38) Fall 2019DO - 10.14505//jemt.v10.6(38).14, 2019)
The relevance of the research is due to the need of domestic enterprises of the hotel industry for periodically making managerial decisions to improve the profitability of their activities. In this regard, the aim of the article is to develop a comprehensive multifactorial and multiplicative model for evaluating the efficiency of reproduction processes of fixed assets of hotel enterprises. The main method of studying this problem is the method of econometric modeling which allows to evaluate the impact of the processes of use and reproduction of fixed assets of enterprises on the profitability of the business entity, develop ways of effective management and substantiate the prospective (forecast) indices of enterprise development. The building algorithm is substantiated and complex multi-factor multiplicative model for evaluating the impact of the state and effectiveness of fixed assets on the profitability of hotel companies is developed. The forecast values of profitability of hotel services given the indices of movement and efficiency of use of fixed assets at the enterprises of hotel industry are obtained for the short-term prospect. The presented model will allow the enterprises of hotel industry to determine ways of reproduction, renewal and modernisation of fixed assets for ensuring high quality of hotel services and increase of profitability of activity at large.